Dynamic thermal modelling of horizontal ground-source heat pumps - Gan, Guohui (Oxford University Press, 2013)
A computer program has been developed for numerical simulation of the dynamic thermal performance of horizontally coupled heat exchangers for ground-source heat pumps, taking account of dynamic variations of climatic, load and soil conditions. The program was used to investigate the effects of operating and start times, installation depth and soil freezing on the heat exchanger performance. It is shown that the rate of heat extraction decreases with increasing operating time. Operating a heat pump with an earlier start date in autumn would give rise to a higher amount of cumulative heat extraction. Also, a heat exchanger installed at a shallower depth can provide a larger heat extraction rate at the early stage of heating operation. In addition, soil freezing enhances heat extraction.